2019
DOI: 10.7759/cureus.5666
|View full text |Cite
|
Sign up to set email alerts
|

The Necessity of a Colonoscopy after an Acute Diverticulitis Event in Adults Less Than 50 Years Old

Abstract: IntroductionAcute diverticulitis is defined as a macroscopic inflammation of a diverticulum or diverticula. Approximately, 4.0% of patients with diverticulosis present with an acute diverticulitis event: with the incidence increasing in the younger patient population. According to the American Gastrointestinal Association, a colonoscopy should be performed six to eight weeks after resolution of acute diverticulitis. The purpose of this study is to determine if there is malignancy after an acute diverticulitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…A total of 68 studies with 13 905 patients were included 6,24–90 . There were four prospective studies and one retrospective review of a prospective study 44,60,61,77,89 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 68 studies with 13 905 patients were included 6,24–90 . There were four prospective studies and one retrospective review of a prospective study 44,60,61,77,89 .…”
Section: Resultsmentioning
confidence: 99%
“…There were 13 296 patients from 65 studies who underwent a follow up colonoscopy 6,24–42,44–65,67–79,81–90 . The remaining three studies (231 patients) reported follow up with either a colonoscopy or flexible sigmoidoscopy and did not differentiate between the two 43,66,80 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations